Raman Spectroscopic and Sensory Evaluation of Cocoa Liquor Prepared with Ecuadorian Cocoa Beans Treated with Gamma Irradiation or Induced Electromagnetic Field Fermentation - Tania María Guzmán-Armenteros; Jenny Ruales; Cristina Cuesta-Plúa; Juan Bravo; Marco Sinche; Edwin Vera; Edison Vera; Paul Vargas-Jentzsch; Valerian Ciobotă; Fernando E. Ortega-Ojeda; Andrés Proaño; Armando Echeverría; et al. (Foods, 2023)
Cocoa liquor is the primary precursor of the worldwide highly appreciated commodity chocolate. Its quality depends on several factors, such as the type of cocoa, the fermentation process, and the control of the contaminants in the fermented beans. This study aims to evaluate whether the induced magnetic field treatment during the fermentation process or the pathogen reduction with gamma irradiation after the fermentation affect the characteristics of the cocoa liquor obtained from Ecuadorian cocoa beans. For this purpose, liquor samples from controls (standard process), from beans treated with an induced magnetic field up to 80 mT, and from beans irradiated with nominal doses up to 3 kGy were characterized through Raman spectroscopic analysis and sensorial evaluation. The most relevant bands of the cocoa liquor were assigned according to reports from the literature, spectroscopic data, and chemometrics. The spectra corresponding to different treatments and doses were visually very similar, but they could be discriminated using OPLS-DA models, where the most intense Raman signals were attributed to the lipid components. The sensorial evaluation rated the presence of floral, fruity, almondy, acid, and bitter flavors, along with astringency and intense aroma, and these attributes exhibited variable behavior depending on the dose of the irradiation or magnetic treatment. Therefore, both treatments may exert an influence on cocoa beans and, therefore, on the cocoa liquor quality.